(untitled) (Annals of Medical Research, 2021)
Aim: Preeclampsia is a pregnancy-specific syndrome associated with vascular spasm and endothelium dysfunction that leads to reduced organ blood flow. Migraine is a syndrome of benign recurrent headaches, nausea, vomiting, or other signs of neurologic dysfunction. Some studies have shown that women who have a history of migraines during pregnancy are at high risk of preeclampsia. The aim of this was determine the relation between migraine and hypertensive disorders of pregnancy. Material and Methods: In this case- control study, cases consisted of 100 women with preeclampsia, and controls were 100 normotensive women. All women were hospitalized in Ardabil city hospital and all of them were evaluated for any history of migraine. The two groups were matched for confounding factors. The data were collected by questionnaire including demographic, medical, obstetrics, and migraine assessment sections. Data were analyzed by statistical methods using SPSS version 19.Results: The mean age of women in study group was 28.12±6.50 and in control group was 25.2±5.75. Majority of persons in the study, were in age group16 to 35 years old and their education levels were high school graduates and they were housewives. The mean of BMI was 24.8. Of people, 11% were suffering from migraine. The history of migraine in the study group was 16% and in the control group was 6% and the difference was significant between two groups (p=0.001). History of migraine headaches in patients with hypertensive disorders was 2.65 times more than women in control group. Conclusion: Results showed that migraine headaches to be associated with gestational hypertension and history of any migraine could be as a risk factor for PE /gestational hypertension (GH) in future. Keywords: Gestational hypertension; migraine; preeclampsia.